HUBUNGAN ANTARA KUALITAS PELAYANAN DENGAN LOYALITAS PASIEN DI POLI BEDAH RSUD dr. R. KOESMA TUBAN - Lukman Hakim; Hyan Oktodia Basuki; Mokhamad Nurhadi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Loyalty patient is a patient's willingness to re-use the health care services provided by the hospitals or health clinics. Loyalty patients can occur due to several factors such as good quality service. Therefore, the study aims to determine the correlation between service quality and loyalty of the patients at the surgical departement of RSUD dr. R. Koesma Tuban. The research used a correlational design with cross-sectional approach involving 71 respondents drawn by accidental sampling technique. Data was taken from the questionnaire. Data were analyzed with the contingensi coefficient test. The result showed most respondents have assumed that the hospital by has intermediate (63,4%) and most of the respondents have less loyalty, there are 46.5%. SPSS results showed that H1 is accepted, so there is a correlation between service quality and loyalty of patients ( ρ = 0.000, which obtained a significant value ≤ 0.005). It can be concluded that there is a correlation between service quality and patient loyalty. The description above can be concluded that service quality can affect patient loyalty. Therefore, it is expected the hospital can increase the ISO (International Organization for Standardization) for the sake of good quality and patient satisfaction for the hospital’s income in the future.